2017
DOI: 10.18632/oncotarget.22062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperthermic intrathoracic chemotherapy on the malignant pleural mesothelioma: a systematic review and meta-analysis

Abstract: Surgery-based multimodality therapies have been used to control the malignant effusion and its recurrence in malignant pleural mesothelioma (MPM). Hyperthermic intrathoracic chemotherapy (HITHOC) has been used in the treatment of malignant pleural mesothelioma, but the results were controversial. The aim of the current study was, therefore, to conduct a systematic review and meta-analysis on the effect of HITHOC on MPM therapy. After thorough searching of online databases, total 21 articles were included into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
1
28
0
3
Order By: Relevance
“…One developing area in the management of pulmonary complications, including malignant pleural effusions, is the use of hyperthermic pleural/intrathoracic chemotherapy, following the model used successfully for intraperitoneal management of malignant ascites. A systematic review showed some evidence that this improves symptoms but may influence length of survival in those treated, including breast and ovarian cancer patients . There is additional research into pressurized intrathoracic sprays of chemotherapy, which also shows promise.…”
Section: Changing Patterns In Management Of Symptoms and Timing Of Inmentioning
confidence: 99%
See 1 more Smart Citation
“…One developing area in the management of pulmonary complications, including malignant pleural effusions, is the use of hyperthermic pleural/intrathoracic chemotherapy, following the model used successfully for intraperitoneal management of malignant ascites. A systematic review showed some evidence that this improves symptoms but may influence length of survival in those treated, including breast and ovarian cancer patients . There is additional research into pressurized intrathoracic sprays of chemotherapy, which also shows promise.…”
Section: Changing Patterns In Management Of Symptoms and Timing Of Inmentioning
confidence: 99%
“…A systematic review showed some evidence that this improves symptoms but may influence length of survival in those treated, including breast and ovarian cancer patients. 23 There is additional research into pressurized intrathoracic sprays of chemotherapy, which also shows promise. This option is targeted more toward early palliation when starting initial or second-line therapy and not when managing terminal pulmonary issues.…”
Section: Pulmonary Symptomsmentioning
confidence: 99%
“…Thorough preoperative assessment for chemotherapy-induced toxicity and prehabilitation improve the postoperative outcome and aids in perioperative management. [ 5 ] Chemotherapeutic agents commonly used in HIPEC and HITHOC include cisplatin, doxorubicin, oxaliplatin, and mitomycin C.[ 6 ] These patients can have diminished cardiopulmonary reserve due to the presence of pleural effusion, ascites, or cardiotoxicity from chemotherapeutic agents. The pathophysiological changes in various organs as well as metabolic and electrolyte disturbances are almost similar in HIPEC and HITHOC with a few additional risks related to HITHOC [ Table 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only selected patients can benefit from a complete resection, either lungsacrificing surgery (extrapleural pneumonectomy, EPP) or lung-sparing (pleurectomy/decortication, P/D) (11)(12)(13). Surgery can be coupled with intraoperative treatments (14)(15)(16)(17), but a general consensus on the proper multimodality approach is lacking.…”
Section: Mesothelioma Therapies Standardmentioning
confidence: 99%